Das Imperium als historischer Auftrag –: Geschichtsbilder auf der Weltausstellung von St. Louis, 1904 - Schumacher, Frank (Comparativ, 2009)
Ethnographic displays were an integral feature of many of the World’s Fairs and international expositions. The display of ‘exotic’ races typically advanced powerful messages of civilizatory supremacy intended to provide imperial self-assurance and entertainment for the colonial metropolis. At the St. Louis World’s Fair of 1904 such anthropological exhibits reached unknown heights. The fair’s organizers hoped to introduce visitors to a coherent re-interpretation of the nation’s history of expansion and thus emphasized the perceived differences between European and U.S. approaches to colonial state-building. By grouping native Americans and Filipinos side-by-side, the fair underlined the benefits of a paternalistic ideology of uplift through education and re-interpreted the colonial project as an anti-colonial civilizing mission. Despite this emphasis on the perceived merits of the ‘benevolent assimilation’ of the colonial ‘other’, however, the fair’s daily reality with its pervasive racism and strong exoticism subverted, complicated, and contradicted this exercise in colonial imagination.